The Design of a New Cobalt Sulfide Nanoparticle Implanted Porous Organic Polymer Nanohybrid as a Smart and Durable Water‐Splitting Photoelectrocatalyst. Issue 59 (26th September 2017) - Shit, Subhash Chandra; Khilari, Santimoy; Mondal, Indranil; Pradhan, Debabrata; Mondal, John
Abstract: Development of an inexpensive, efficient and robust nanohybrid catalyst as a substitute for platinum in photoelectrocatalytic hydrogen production has been considered intriguing and challenging. In this study, the design and sequential synthesis of a novel cobalt sulfide nanoparticle grafted Porous Organic Polymer nanohybrid (CoS x @POP) is reported and used as an active and durable water‐splitting photoelectrocatalyst in the hydrogen evolution reaction (HER). The specific textural and relevant chemical properties of as‐synthesised nanohybrid materials (Co3 O4 @POP &CoS x @POP) were investigated by means of XRD, XPS, FTIR, 13 C CP MAS NMR, spectroscopy, HR‐TEM, HAADF‐STEM with the corresponding elemental mapping, FE‐SEM and nitrogen physisorption studies. CoS x @POP has been evaluated as a superior photoelectrocatalyst in HER, achieving a current density of 6.43 mA cm −2 at 0 V versus the reversible hydrogen electrode (RHE) in a 0.5 m Na2 SO4 electrolyte which outperforms its Co3 O4 @POP analogue. It was found that the nanohybrid CoS x @POP catalyst exhibited a substantially enhanced catalytic performance of 1.07 μmol min −1 cm −2, which is considered to be ca. 10 and 1.94 times higher than that of pristine POP and CoS x, respectively. Remarkable photoelectrocatalytic activity of CoS x @POP compared to Co3 O4 @POP toward H2 evolution could be attributed to intrinsic synergistic effect of CoS x and POP, leading to the formation of a unique CoS x @POP nanoarchitecture with high porosity, which permits easy diffusion of electrolyte and efficient electron transfer from POP to CoS x during hydrogen generation with a tunable bandgap, that straddles between the reduction and oxidation potential of water. Abstract : Water splitting photocatalyst : A noble metal free cobalt sulfide nanoparticle grafted Porous Organic Polymer nanohybrid (CoS x @POP) has been developed as an active and durable water‐splitting photoelectrocatalyst for the hydrogen evolution reaction.